Máku a comprehensive grammar - Rogers, Chris 1977- (Routledge comprehensive grammars, 2021)
Máku: A Comprehensive Grammar is a comprehensive reference grammar of the Maku language, spoken by the jukudeitse who once lived in Venezuela and Brazil. Based on fieldwork with the final two speakers of the language, it describes all core aspects of the grammatical system as they have been recorded; presented through lexical items, example sentences and texts. This book offers a description of the now-extinct language. It was written in response to the loss of linguistic information generally and the significance this language has for the study of the sociolinguistic history of the region specifically. This information contributes to our understanding of linguistic diversity and the indigenous linguistic ecologies in the Americas. Also included is data about language contact via loanwords with other indigenous language spoken in the Northern Amazonian region. The resources in this book are essential for language comparisons and language histories in Venezuela and Brazil.Máku: A Comprehensive Grammar is an important reference for researchers and students in the fields of linguistics, anthropology, sociology, history and the study of Amazonian languages